2007
DOI: 10.2319/052906-215
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of Temporomandibular Disorders before and after Orthognathic Surgery

Abstract: Objective: To answer the question whether orthognathic surgery does affect the prevalence of signs and symptoms of temporomandibular disorders (TMDs). Materials and Methods: A literature survey in the PubMed and Cochrane Library electronic databases was performed and covered the period from January 1966 to April 2006. The inclusion criteria were controlled, prospective or retrospective studies comparing TMDs before and after orthognathic surgery in patients with malocclusion. There were no language restriction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
10

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 19 publications
0
22
0
10
Order By: Relevance
“…A caracterização da amostra, predominando deficiência mandibular e excesso maxilar com cirurgias bimaxilares foi similar a outros estudos 1,11,12,29 . As queixas principais encontradas na etapa pré-cirúrgica foram muitas e variadas como apontam estudos anteriores 4,10,14,23 , constatando-se redução significativa das queixas funcionais e estética após quatro meses dos tratamentos. Esses dados vão de acordo com estudos que analisam o papel do reposicionamento cirúrgico das bases ósseas e da fonoterapia na reabilitação por meio do direcionamento miofuncional 5,9,10,21 .…”
Section: Resultsunclassified
See 2 more Smart Citations
“…A caracterização da amostra, predominando deficiência mandibular e excesso maxilar com cirurgias bimaxilares foi similar a outros estudos 1,11,12,29 . As queixas principais encontradas na etapa pré-cirúrgica foram muitas e variadas como apontam estudos anteriores 4,10,14,23 , constatando-se redução significativa das queixas funcionais e estética após quatro meses dos tratamentos. Esses dados vão de acordo com estudos que analisam o papel do reposicionamento cirúrgico das bases ósseas e da fonoterapia na reabilitação por meio do direcionamento miofuncional 5,9,10,21 .…”
Section: Resultsunclassified
“…A ocorrência de sinais e sintomas de disfunções temporomandibulares em pacientes com deformidades dentofaciais tem sido largamente discutida na literatura 1,2,4,9,[10][11][12][13][14] . Diversos estudos indicam maior incidência de sinais de alteração da articulação temporomandibular (ATM), tais como estalos, dor orofacial e redução da amplitude dos movimentos mandibulares, gerando maior dificuldade na realização das funções estomatogná-ticas 2,8,9,[15][16][17] , principalmente nos indivíduos com Classe II esquelética [18][19][20] .…”
Section: Introductionunclassified
See 1 more Smart Citation
“…5 Abrahamsson et al 6 reported in a systematic review that no conclusion could be drawn if and how orthognathic surgery alters signs and symptoms of TMD. However, IVRO or modified condylotomy has been reported favorable to the TMJ because of the anteriorinferior repositioning of the condyle and the increase in joint space, with a chance of improved symptoms of the joint.…”
Section: The Adaptation Of the Surgical Techniquementioning
confidence: 99%
“…De resultaten van deze behandeling zijn nooit in de wetenschappelijke literatuur gepubliceerd. Later werden juist de capita mandibulae minutieus op hun plaats gehouden tijden de chirurgische behandeling, maar of dat zinvol was viel te betwijfelen (Abrahamsson et al, 2007;Costa et al, 2008 De gevolgen van een osteotomie van de onderkaak op het temporomandibulaire gewricht en op het ontstaan of verdwijnen van temporomandibulaire disfunctieklachten zijn slecht voorspelbaar, maar vrouwen met een korte en steile onderkaak en van degeneratie verdachte capita mandibulae vormen een risicogroep bij een verlenging van de onderkaak (Hoppenreijs et al, 1998). De capita mandibulae zouden volledig kunnen resorberen.…”
Section: Beschouwingunclassified